ICT as moderating factor toward determinants of female labour force participation in Negeri Sembilan / Nadhrah Rosman - Rosman, Nadhrah (Faculty of Business and Management, 2018)
This study examines the relationships that between Female Labour Force Participation and its determinants Education (EDU), Marriage (MAR) and Childcare cost (CHILD) if there is Accessibility of ICT as moderating variable among women at the working age of 15 to 50 years old. This paper applies Multiple Linear Regression analysis method to define the statistical relationship among the variables. Besides, there are several steps involved in the study which are frequency analysis, descriptive analysis, Pearson correlation and Single Linear Regression analysis method. The result of the study will be analyse using SPSS. The result of this study shows that there is a significant relationship between Female Labour Force Participation in Negeri Sembilan (FLFP) and education (EDU), marriage (MAR) and Childcare cost (CHILD) if Accessibility of ICT become the moderating variable. The conclusion for the studies shows that accessibility of ICT can be the moderating factor towards the determinants of female labour force participation in Negeri Sembilan.